PENGGUNAAN METODE EVERYONE IS A TEACHER DAPAT MENINGKAT KAN KEAKTIFAN SISWA KELAS V SD NEGERI 137957 KOTA TANJUNGBALAI - Simbolon, Lasta Murni (Jurnal Sabilarrasyad, 2021)
This study aims to determine: 1) The use of the Everyone is a teacher method can increase the activity of the fifth grade students of SD Negeri 137957 Kota Tanjungbalai; 2) The use of the Everyone is a teacher method can improve social studies learning achievement in grade V SD Negeri 137957 Kota Tanjungbalai. This type of research is PTK ata Classroom Action Research. Subject SD Negeri 137957 Kota Tanjungbalai. The results showed that the use of the everyone is a teacher type of active learning method can increase activeness. the results of the percentage of pre-action in the observed aspects had not reached ≥ 66.7%. In the first cycle there was an increase in each observed aspect, but it still did not reach ≥ 66.7%. In the second cycle there was an increase again in each observed aspect and it had reached ≥ 66.7%. The use of the everyone is a teacher type of active learning method can improve learning achievement. With the results of pre-action the percentage of completeness is 16.67% with an average of 48.66, there is an increase in the first cycle the percentage of completeness is 41.66% with an average of 64.38, and in the second cycle it has increased again with a percentage of 87.50 % and an average of 84.76.